A Novel MicroRNA From the Translated Region of the Giardiavirus rdrp Gene Governs Virus Copy Number in Giardia duodenalis - Gong, Pengtao; Li, Xianhe; Wu, Wei; Cao, Lili; Zhao, Panpan; Li, Xin; Ren, Baoyan; Li, Jianhua; Zhang, Xichen (Frontiers in Microbiology, 2020)
Giardia duodenalis is an important zoonotic parasite that can cause human and animal diarrhea. Giardiavirus (GLV) is a double strand RNA virus in Totiviridae family, which specifically infects trophozoites of the primitive protozoan parasite Giardia duodenalis. However, the GLV infectious and the pathogenicity of the Giardia duodenalis still remain to be confirmed. The GLV genome is 6277bp, which encodes two proteins (Gag and Gag-Pol). The expression of Gag-Pol protein is regulated by a-1 ribosomal frame shift. In this report, we identified a novel microRNA (GLV miRNA1) from the GLV. Split ligation northern results showed that GLV miRNA1 is a special expression product of GLV, and the precursor was also identified by primer extension. Antisense sequence of the GLV miRNA1 could increase the copy number of virus in G. duodenalis. It suggests that GLV miRNA1 governs the copy number of giardiavirus in Giardia duodenalis. Most importantly, the GLV miRNA1 lies at the translated region of the rdrp gene, which is the first case that microRNA locates in the translated region of a known protein. It may be implying a novel phenomenon for miRNA biogenesis.